Maldi-target integrated microfluidic PSA assay - Tajudin, Asilah Ahmad; Ekstrom, Simon; Jaras, Kerstin; Marko-Varga, Gyorgy; Malm, Johan; Lilja, Hans ; 0000-0001-5871-7846; Laurell, Thomas (13th International Conference on Miniaturized Systems for Chemistry and Life Sciences, MicroTAS 2009, Jeju, Korea, Republic of, 2009-11-01 - 2009-11-05, 2009)
An Integrated Selective Enrichment Target (ISET), microfabricated for efficient on-bead enzymatic digestion of proteins compatible for a direct interface with matrix-assisted laser desorption /ionization mass spectrometry (MALDI MS) is presented.
Keywords: ISET; MALDI MS; On-bead protein digestion; Proteomic; PSA; Sample preparation